Analisis Peningkatan Mutu Pendidikan melalui Penggunaan Literasi Digital pada Madrasah Aliyah Negeri di Provinsi Aceh - Amiruddin Amiruddin; Azhari Azhari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The obligations of teachers in Madrasahs are complex. The Ministry of Religion of Aceh Province as the protector of teachers who work in Madrasahs has provided various trainings for teachers. One of them is the collaboration between the Ministry of Religion of Aceh Province and USAID PRIORITAS in a number of Madrasahs in Aceh. Based on these activities, it turns out that they are still unable to provide accurate answers about Madrasahs in Aceh Province. Where many cannot be studied in depth about professional development for all teachers in the Ministry of Religion of Aceh Province. Every educational institution must have infrastructure. The infrastructure that is directly related to teaching is the classroom. These basic facilities are one of the media to carry out Madrasah functions. The study room is a space for theoretical and practical learning that does not require special equipment. Classroom management is a prerequisite as well as the most important aspect in realizing effective learning. This is done to refer to the creation of an atmosphere or class condition that allows students to carry out the learning process effectively and pleasantly. So that the integration between digital literacy and the need for materials and teaching materials has not been fully able to meet the sources and teaching materials at Madrasah Aliyah, this condition is related to the readiness of expertise for educators in producing digital literacy innovations that can be adapted to teaching materials and materials based on the applicable curriculum. The use of digital literacy has an influence on the analysis of the quality of madrasa education. Institutional regression results have an effect of 14.3% and madrasah have an influence of 66.2%.